2010
DOI: 10.1111/j.1439-0396.2010.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Chewing patterns and digestion in sheep submitted to feed restriction

Abstract: Two experiments were conducted to evaluate the relationship among the level of feed intake, chewing pattern, and diet digestibility in sheep fed a moderate-concentrate diet. The first experiment was conducted using six male lambs at a replicated 3 × 3 Latin square design to evaluate diet digestibility and microbial N synthesis according to the level of intake: ad libitum, or restricted to either 70 or 55% of the ad libitum intake. In the second experiment, fifteen male lambs were housed in individual stalls, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
4
12
0
1
Order By: Relevance
“…With regard to digestibility, the results are consistent with those described by Galvani et al (2010) and Dias et al (2011) who observed, respectively, higher DMD and nutrient digestibility in sheep and cattle subjected to feed restriction. The lowest DC presented by the ad libitum treatment may be explained due to the increase in the passage rate of feed particles through the reticulum-rumen and the lower retention time of digesta through the gastrointestinal tract due to the higher level of DM (Dias et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With regard to digestibility, the results are consistent with those described by Galvani et al (2010) and Dias et al (2011) who observed, respectively, higher DMD and nutrient digestibility in sheep and cattle subjected to feed restriction. The lowest DC presented by the ad libitum treatment may be explained due to the increase in the passage rate of feed particles through the reticulum-rumen and the lower retention time of digesta through the gastrointestinal tract due to the higher level of DM (Dias et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…A similar result was described by Cândido et al (2012), who observed higher values of REDM and RENDF in cattle fed ad libitum compared with those submitted to feed restriction. Galvani et al (2010) also observed greater RTDM in lambs subjected to feed restriction. The highest values of RTDM and RTNDF obtained with dietary restriction may be related to higher ruminal retention of feed particles, caused by the lower level of intake, which is an adaptive mechanism of ruminants to provide greater nutrient digestibility under conditions of feed restriction (Dias et al, 2011).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Horses do not appear to compensate for a low amount of food by an increased chewing intensity, and, in contrast to reports in ruminants (Shaver et al., ), chewing efficiency does not seem to be compromised at high intake levels. The numerical increase in particle size with decreasing intake level could be an effect of a disproportionately hasty ingestion in hungry animals, as reported in sheep on low food intake levels (Galvani et al., ). An increase in chewing intensity with forage fibre content has been reported previously in horses (Janis et al., ); the finer mean particle size measured on hay 2 in this study matches this pattern, as does the un‐quantified observation of generally longer feeding times on this hay.…”
Section: Discussionmentioning
confidence: 76%
“…In sub‐Saharan Africa, cattle are regularly exposed to situations of undernutrition due to limited availability of feed, often coupled with low crude protein (CP) and high neutral and acid detergent fibre (NDF, ADF) concentrations during the long dry season (Angassa & Beyene, ; Bezabih, Pellikaan, Tolera, Khan, & Hendriks, ; Debele, Guru, Hundessa, & Duguma, ). At feeding levels above or close to maintenance energy requirements (MER), low feed intake has been shown to increase rumination time (Galvani, Pires, Wommer, Oliveira, & Santos, ), the percentage of fine feed particles in solid digesta (Luginbuhl, Pond, & Burns, ; Okine & Mathison, ) and overall diet digestibility (Galvani et al, ; Schulze, Weisbjerg, & Nørgaard, ). In Holstein steers fed grass silage and soybean hulls, Mulligan et al () observed a decline of the ruminal passage rate of solid digesta and a concomitant increase in the digestibility of dry matter (DM), organic matter (OM), CP, NDF and ADF as feed intake decreased from 160% to 100% MER.…”
Section: Introductionmentioning
confidence: 99%